Director experience, management compensation and tax avoidance - Sri Asih; Doddy Setiawan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
The purpose of this study is to analyze the effect of director experience and management compensation on tax avoidance in Indonesia. This is quantitative research with secondary data sources using cross section data. Purposive sampling was used to obtain 267 observation samples of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020 tested using multiple linear regression analysis. Dependent variable of tax avoidance proxied by cash effective tax rate is used. The director’s experience and management compensation are independent variables in this study. The director’s experience is measured by using the dummy variable of the director’s experience during study or work abroad. Management compensation is proxied by using the natural logarithm of the annual compensation received by management. Some control variables are also used such as firm size, leverage, firm age, return on assets, growth, market to book ratio, and debt to equity ratio. We found that there is a significant negative relationship between director's experience and management's compensation on tax avoidance. In conclusion, director's experience and management compensation are both important for tax avoidance decisions in companies.